Vindicating Realist Internationalism. Issue 5 (3rd September 2021) - Lieven, Anatol
Abstract: Liberal internationalists, such as professors Daniel Deudney and G. John Ikenberry, share much of the neoconservatives' international agenda while disagreeing with them on domestic policies. Likewise, the members of what they call the 'Quincy coalition' agree on opposing US interventionism and military domination without necessarily agreeing on other issues. Those at the Quincy Institute for Responsible Statecraft are internationalists in that we believe firmly in international cooperation in pursuit of essential common goals, such as limiting climate change. We also believe, however, that pursuing these goals through US domination hinders rather than advances their achievement. Liberal internationalism as envisaged by Deudney and Ikenberry is intrinsically linked to US hegemony and one form of American ideological nationalism. They share responsibility for the disasters that these have caused, and for the growing confrontation with China that threatens to wreck prospects for a peaceful and consensual global order.